Myeloid Cell CK2 Regulates Inflammation and Resistance to Bacterial Infection - Larson, Sandy R.; Bortell, Nikki; Illies, Alysha; Crisler, William J.; Matsuda, Jennifer L.; Lenz, Laurel L. (Frontiers in Immunology, 2020)
Kinase activity plays an essential role in the regulation of immune cell defenses against pathogens. The protein kinase CK2 (formerly casein kinase II) is an evolutionarily conserved kinase with hundreds of identified substrates. CK2 is ubiquitously expressed in somatic and immune cells, but the roles of CK2 in regulation of immune cell function remain largely elusive. This reflects the essential role of CK2 in organismal development and limited prior work with conditional mutant murine models. Here, we generated mice with a conditional (floxed) allele of Csnk2a, which encodes the catalytic CK2α subunit of CK2. When crossed to Lyz2-cre mice, excision of Csnk2a sequence impaired CK2α expression in myeloid cells but failed to detectably alter myeloid cell development. By contrast, deficiency for CK2α increased inflammatory myeloid cell recruitment, activation, and resistance following systemic Listeria monocytogenes (Lm) infection. Results from mixed chimera experiments indicated that CK2α deficiency in only a subset of myeloid cells was not sufficient to reduce bacterial burdens. Nor did cellintrinsic deficiency for CK2α suffice to alter accumulation or activation of monocytes and neutrophils in infected tissues. These data suggest that CK2α expression by Lyz2-expressing cells promotes inflammatory and anti-bacterial responses through effects in trans. Our results highlight previously undescribed suppressive effects of CK2 activity on inflammatory myeloid cell responses and illustrate that cell-extrinsic effects of CK2 can shape inflammatory and protective innate immune responses.